Gestational Low Protein Diet Modulation on miRNA Transcriptome and Its Target During Fetal and Breastfeeding Nephrogenesis - de Barros Sene, Letícia; Lamana, Gabriela Leme; Schwambach Vieira, Andre; Scarano, Wellerson Rodrigo; Gontijo, José Antônio Rocha; Boer, Patrícia Aline (Frontiers in Physiology, 2021)
Background: The reduced nephron number is predictive of hypertension and cardiovascular dysfunctions that are generally observed in the adult age of the most fetal programming models. Recently, in the 17 gestational days (17GD) low protein (LP) intake male fetal kidney, we demonstrate changes in miRNAs and predicted molecular pathways that led to reduced reciprocal interaction between metanephros cap (CM) and ureter bud (UB). Here, we evaluated the same miRNAs and predicted targets in the kidneys of 21GD and at 7 days of life (7DL) LP offspring to elucidate the molecular modulations during nephrogenesis. Methods: Pregnant Wistar rats were allocated into two groups: NP (regular protein diet- 17%) or LP (diet-6%). miRNA transcriptome sequencing (miRNA-Seq) was performed on the MiSeq platform from 21GD and 7DL male offspring kidneys using previously described methods. Among the top 10 dysfunctional regulated miRNAs, we validated 7 related to proliferation, differentiation, and apoptosis processes. Results: In 21GD, LP fetuses were identified twenty-one differently expressed miRNAs, which 12 up- and 9 downregulated, compared to age-matched NP offspring. In 7-DL LP offspring, the differentially expressed miRNAs were seventy-four, which 46 up- and 28 downregulated. The curve from 17-GD to 7-DL shows that mTOR was fundamental in reducing the number of nephrons in fetal kidneys, whose mothers were subjected to a protein restriction. IGF1 and TGFβ curves seemed to present the same mTOR pattern and were modulated by miRNAs 181a-5p, 181a-3p, and 199a-5p. miRNA 181c-3p modulated SIX2 and Notch1 reduction in 7-DL, but not the enhanced expression of both in the 21-GD, suggesting an additional regulator's participation. We found in 21-GD enhanced Bax, regulated by miRNA 298-5p, and Bcl2 and Caspase 3 controlled by miRNA, let 7a-5p and not by 181a-5p how predicted. The miRNA 144-3p regulated BCL6 that was enhanced as well as Zeb 1 and 2 induced by BCL6. In the 21GD, compensatory mechanisms led to the activation of UB ramification, an increase of 32% in the CM stem cells, and a possible cell cycle arrest with the migration of undifferentiated cells during nephrogenesis. The activation of pathways related to differentiation and cell progenitor consumption was showed.